ANALISIS ATTRIBUTION ERROR PADA SISWA KELAS 5 SEKOLAH DASAR NEGERI KELAPADUA KOTA SERANG - Emar Mardhatilah; Ajo Sutarjo; Muhammad Hanif (Universitas Tanjungpura, 2022)
Attribution theory is study of individual can assume behind the behavior of others. A result, attribution theory can be deeply ingrained the study of education, which focuses on the result of student behavior in the form of success or failure. However, looking the current conditions, especially the problems found at SDN Kelapadua, there are deviations attribution theory that make grade 5 students make mistakes in attributing the behavior of other students. Based on the survey data, the researcher chose student G as subject of study because it was suspected that he had received the most attribution errors in the class. The researcher used a qualitative technique and case study method to analyze the attribution error case that occurred student G in this study. The research takes place in SDN Kelapadua Serang City, subject of the study is student G, a grade 5 student. Interviews, observations, and document studies were employed to acquire data for this study. According to the findings of this study, student G has minority behaviors that are deemed to interfere with learning process in the classroom, student G communication skills and courage are deemed inadequate, and student G emotional management ability still deemed inadequate when interacting with other students. Other persons and their particular selves cause the type of attribution error that occurs in student G. The type of attribution error that occurs in student G is caused by other individuals and their particular selves. Other people's attribution faults include: Fundamental Attribution Error, Actor Observer Effect, Hedonic Relevance, and Egocentric Bias. Meanwhile, self-serving bias and self-blame attribution are examples of attribution errors made by student G. Furthermore, student G exhibits behavior with high uniqueness, consistency, and low consensus, implying that the attribution error in student G is driven by an internal-external component.